Euryops chrysanthemoides African Bush Daisy, Bull's Eye, Bush Daisy: FPS-220/FP220, 5/2007 - Gilman, Edward; Landrum, Linda (EDIS, 2007)
This document provides an overview of the African bush daisy (Euryops chrysanthemoides), detailing its characteristics, growth requirements, and uses. The plant is a perennial shrub native to Africa, known for its bright yellow flowers and fern-like leaves. It thrives in full sun and various soil types, with moderate drought tolerance. The African bush daisy is suitable for mass planting, borders, and containers, attracting butterflies and requiring occasional clipping for dense growth. It is somewhat available and can be propagated by seed, with nematodes being the primary pest concern. Original publication date October 1999.